THE POTENTIAL OF PROFILING TECHNOLOGY IN PREVENTING CRIMES RELATED TO HONOR - Musurmankulova Iroda Zulpikhorovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Honor related crimes remain a critical social issue influenced by deep-rooted cultural and societal norms. This article explores the potential of profiling technology as a proactive tool for preventing such crimes. By analyzing behavioral patterns, social interactions, and psychological indicators through advanced data analytics and artificial intelligence, profiling technologies can aid in early identification of high-risk individuals and situations. While offering promising capabilities for intervention and resource optimization, the use of profiling in this context raises significant ethical and cultural concerns. The study emphasizes the importance of integrating profiling tools with legal frameworks, community involvement, and victim support to ensure effective and respectful prevention strategies. Ultimately, a balanced multidisciplinary approach is essential to address the complexities of honor-related violence.